Numerical Evaluation on Massif Vibration of Pumped Storage Power Plant in Hydraulic Transients - Tao Wang; Hongfen Tang; Hongsheng Chen; Dong Ma; Yuchuan Wang; Honggang Fan (Energies)
This research aims to assess the massif vibration that results from hydraulic transitions of pumped storage power plant (PSPP) and probe into their consequences on mountain stability. Firstly, numerical simulations of the hydraulic transitions in a pumped storage power plant were carried out, and the pressure pulsations within different sections of the waterway system under pumping and generating conditions were obtained. The historical pressure during the hydraulic transients was used as the dynamic loading condition for transient structural analysis. The time-history curves of horizontal and vertical accelerations were obtained for four main working conditions, and four detection areas were demarcated on the massif surface for analysis. The results showed that the maximum amplitude of horizontal acceleration occurred within the height range of 760 m to 960 m of work condition T2. Statistical methods and one-third octave analysis were further applied to analyze the acceleration time-history curves, showing that the highest vibration levels in the horizontal direction were observed at a specific frequency of 50 Hz. This study indicates that the hydraulic transition process of pumped-storage power stations will have a significant impact on massif stability; therefore, it is crucial to consider corresponding seismic mitigation measures during the design and operating stages to ensure structural safety.